Procedure for isolation of bacterial lipopolysaccharides from both smooth and rough Pseudomonas aeruginosa and Salmonella typhimurium strains. - Darveau, R P (1983)
Lipopolysaccharide (LPS) is a major component of the outer membrane of gram-negative bacteria. It is now well established that within a single organism, size heterogeneity of this molecule can exist. We have developed a LPS isolation procedure which is effective in extracting both smooth and rough LPS in high yields (51 to 81% of the LPS present in whole cells as quantitated by using hydroxy fatty acid, heptose, and 2-keto-3-deoxyoctonate yields) and with a high degree of purity. The contamination by protein (0.1% by weight of LPS), nucleic acids (1%), lipids (2 to 5%), and other bacterial products was low. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the LPS demonstrated the presence of a high degree of size heterogeneity in the isolated smooth LPS as well as the presence of significant amounts of rough-type LPS. The Pseudomonas aeruginosa LPS interacted well with a monoclonal antibody in a variety of immunochemical analyses. The usefulness of the procedure was demonstrated by comparing LPS preparations obtained from wild-type and mutant strains of P. aeruginosa and Salmonella typhimurium. For example, it was shown that the LPS of an antibiotic supersusceptible mutant Z61 of P. aeruginosa, which was previously characterized as identical to wild type with respect to the ratio of smooth to rough LPS molecules isolated by the phenol-water procedure, actually contained only a small proportion of O-antigenic side chains.